Boundary control : subnational authoritarianism in federal democracies - Gibson, Edward L. (New York : Cambridge University Press, 2012)
'This book explains how subnational authoritarianism is part of normal democratic politics and strategic interactions between local authoritarians and national democratic leaders'--
Machine generated contents note: 1. Introduction; 2. Territorial politics and subnational democratization: charting the theoretical landscape; 3. Subnational authoritarianism in the United States: boundary control and the'Solid South'; 4. Boundary control in democratizing Argentina; 5. Boundary control in democratizing Mexico; 6. Boundary control: comparisons and conclusions.
Includes index and bibliography : pages 173-182.
Keywords: Federal government; Subnational governments; Authoritarianism; Central-local government relations